Medical Image-Based Hemodynamic Analyses in a Study of the Pulmonary Artery in Children With Pulmonary Hypertension Related to Congenital Heart Disease - Wang, Liping; Liu, Jinlong; Zhong, Yumin; Zhang, Mingjie; Xiong, Jiwen; Shen, Juanya; Tong, Zhirong; Xu, Zhuoming (Frontiers in Pediatrics, 2020)
Objective: Pulmonary hypertension related to congenital heart disease (PH-CHD) is a devastating disease caused by hemodynamic disorders. Previous Hhemodynamic research in PH-CHD mainly has focused mainly on wall shear stress (WSS). However, but energy loss (EL) is a vital parameter in evaluation of hemodynamic status. We investigated if EL of the pulmonary artery (PA) is a potential biomechanical marker for comprehensive assessment of PH-CHD. Materials and Methods: Ten PH-CHD patients and ten age-matched controls were enrolled. Subject-specific three-dimensional PA models were reconstructed based on computed tomography. Transient flow, WSS and EL in the PA were calculated using noninvasive computational fluid dynamics. The relationship between body surface area (BSA)-normalized EL (E) and PA morphology and PA flow were analyzed. Results: Morphologic analysis indicated that the BSA-normalized main PA (MPA) diameter (DMPA norm), MPA/aorta diameter ratio (DMPA/DAO) and MPA/(left PA + right PA) (DMPA/D(LPA+RPA)) diameter ratios were significantly larger in PH-CHD patients. Hemodynamic results showed that the velocity of the PA branches was higher in the PA branches of PH-CHD patients, in whom PA flow rate usually increased. WSS in the MPA was lower in the MPA, and E was higher in PH-CHD patients. E was positively correlated with DMPA norm, DMPA/DAO and DMPA/D(LPA+RPA) ratios, and the flow rate in the PA. E was a sensitive index for the diagnosis of PH-CHD. Conclusion: E is a potential biomechanical marker for PH-CHD assessment. This hemodynamic factor parameter may lead new directions for revealing the potential pathophysiologic mechanism of PH-CHD.